OP0232 Sustained safety and efficacy over 10 years with belimumab (BEL) plus standard systemic lupus erythematosus (SLE) therapy (SOC) in patients with SLE. (15th June 2017) - Wallace, DJ; Ginzler, EM; Merrill, JT; Furie, RA; Stohl, W; Chatham, W; Weinstein, A; McKay, J; McCune, WJ; Petri, M; Fettiplace, J; Roth, D; et al.
Abstract : Background: Preliminary safety and efficacy data from the Phase II BEL open-label extension study (LBSL02; NCT00071487 ) have been reported. Objectives: Here we present the final 10-year data. Methods: This was a multicentre, open-label, continuation trial (BEL112626; NCT00583362 ) of BEL + SoC in patients with a satisfactory response in the parent study. Patients received intravenous BEL 10 mg/kg every 4 weeks. Baseline was prior to the first ever dose of BEL. Results: Of 298 patients in the continuation trial, 131 (44%) remained at Year 10. Total BEL exposure was 2154 patient-years. Adverse events (AEs) remained stable or decreased (Table). Two deaths (pseudomonal lung infection; cytomegaloviral pneumonia) were possibly related to BEL. SLE Responder Index (SRI) response increased (Figure). A British Isles Lupus Assessment Group (BILAG) flare (1 new A/2 new B scores) occurred in 72.6% of patients and 41.9% had a severe flare (SLE Flare Index). Prednisone dose decreased from baseline to Year 10 (Table). Of patients receiving >7.5 mg/day baseline prednisone, 32.6% (14/43) decreased their dose to ≤7.5 mg/day by Year 10; 9.5% (9/95) of patients receiving baseline prednisone ≤7.5 mg/day had a dose increase to >7.5 mg/day. Conclusions: Over 10 years BEL + SoC was well tolerated and the rates and nature of AEs were consistent with the known profile of BEL. Efficacy was maintained and prednisone use decreased in those receiving >7.5 mg/day at baseline. Acknowledgements: Study funded by GSK. Editorial assistance provided by Katie White, PhD, Fishawack Indicia Ltd, UK; funded by GSK. Disclosure of Interest: D. Wallace Grant/research support from: GSK, Consultant for: GSK, E. Ginzler Grant/research support from: GSK, J. Merrill Grant/research support from: GSK, Bristol-Myers Squibb, Consultant for: Anthera Pharmaceuticals, Inc., GSK, EMD Serono, Inc., Lilly, AstraZeneca, Bristol-Myers Squibb, UCB, Celgene, Biogen, R. Furie Grant/research support from: GSK, Consultant for: GSK, W. Stohl Grant/research support from: GSK, Pfizer, Consultant for: Johnson & Johnson, W. Chatham Grant/research support from: GSK, A. Weinstein Grant/research support from: GSK, HGS, Consultant for: GSK, HGS, J. McKay Grant/research support from: GSK, MedImmune, Anthera Pharmaceuticals, Inc., Johnson & Johnson, Lilly, Xencor, Inc., W. McCune Grant/research support from: GSK, Lilly, M. Petri Grant/research support from: GSK, Consultant for: GSK, J. Fettiplace Shareholder of: GSK, Employee of: GSK, D. Roth Shareholder of: GSK, Employee of: GSK, B. Ji Shareholder of: GSK, Employee of: GSK, A. Heath Shareholder of: GSK, Employee of: GSK